PENGARUH DISIPLIN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT CIPTA ANEKA AIR - Arisandi, Dewi Tri (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
The purpose of this study is to determine the effect of variable discipline, motivation, and job environment toward employees performance. The research method uses field surveys with a quantitative approach, where the study population was 45 peoples and a sample of 45 peoples. Based on the results of the research and discussion previously stated, the following conclusions are obtained: Test results partially for discipline variables with statistic values ​​tcount > ttable (3.441 > 2.019) and probability values ​​of 0.001 < 0.05, then Ho is rejected means there is influence significant from the discipline variable toward employees performance. Partial test results for motivation variables with a statistic value of tcount > ttable (2.449 > 2.019) and a probability value of 0.019 < 0.05, then Ho is rejected means that there is a significant effect of the motivation variable toward employees performance. Partial test results for job environment variables with a statistic value of tcount > ttable (2.423 > 2.019) and a probability value of 0.020 < 0.05, then Ho is rejected means that there is a significant effect of the job environment variable toward employees performance. Simultaneous test results with a value of Fcount > Ftable (16.210 > 2.830), then Ho is rejected or Ha is accepted which means that there is a significant simultaneous influence (together) of the variable discipline, motivation, and job environment together on the variable employees performance. The magnitude of the correlation coefficient (r) is 0.737 which means that there is a strong correlation between discipline, motivation, and job environment with employees performance. The amount of the adjusted coefficient of determination (adjusted R2) is 0.509 or 50.9%, which means that the independent variables can explain the changes in the variable employees performance by 50.9% while the remaining 49.1% is explained by other factors outside the research this